Theoretical sampling process in a Straussian Grounded Theory study - Mayckel da Silva Barreto; Bruna Sodré Simon; Veronica Francisqueti Marquete; Rebeca Rosa de Souza; Nara Marilene Oliveira Girardon-Perlini; Sonia Silva Marcon (SciELO, 2021)
ABSTRACT Objetive: Describing the theoretical sampling process in the development of a Grounded Theory based on the Straussian strand. The objective of the field research, used as an example, was to develop a substantive theory, based on the theoretical framework of Symbolic Interactionism, about the perceptions and experiences of patients, family members, and health professionals regarding the presence of the family during emergency care. Method: In the theoretical sampling, 42 participants were recruited, divided into nine sample groups, constituted based on the constant comparative method. Results: The description of this example allowed to identify how theoretical sampling guided data collection, which occurred through the in-depth study of concepts and the search for answers to questions arising from the data. Final Considerations: It is expected that the readers find subsidies to understand how theoretical sampling is conducted in a Grounded Theory study, based on the Straussian strand, and thus be able to apply it.